History and Facts about Black Holes - Khatiwoda, Devandra (Himalayan Physics, 2011)
Not available.Key words: Black holesThe Himalayan PhysicsVol.1, No.1, May, 2010 Page: 90-92 Uploaded Date: 28 July, 2011